Markovian Model of the Voltage Gating of Connexin-based Gap Junction Channels - Sakalauskaite, A.; Pranevicius, H.; Pranevicius, M.; Bukauskas, F. (Elektronika ir Elektrotechnika, 2011)
Gap junction (GJ) channels, which are formed of a connexin (Cx) protein provide pathways through which ions and small molecules are exchanged between adjacent cells. GJs co-ordinate the cellular activity in tissues by synchronizing their electrical activity and allowing a direct cell-to-cell chemical signaling. Electrically gap junctions present nonlinear conductance that depends on transjunctional voltage and can be modulated by chemical reagents and ions, such as pH, Ca2+, etc. Here, we describe the model of the voltage gating of gap junctions using Markovian formalism. The results obtained using a stationary Markov model are well comparable with those obtained using a stochastic/imitational model of voltage gating. Ill. 5, bibl. 5, tabl. 3 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.367